1993
DOI: 10.1016/0896-6273(93)90193-u
|View full text |Cite
|
Sign up to set email alerts
|

A novel receptor-type protein tyrosine phosphatase is expressed during neurogenesis in the olfactory neuroepithelium

Abstract: Tyrosine phosphorylation plays a central role in the control of neuronal cell development and function. Yet, few neuronal protein tyrosine phosphatases (PTPs) have been identified. We examined rat olfactory neuroepithelium for expression of novel PTPs potentially important in neuronal development and regeneration. Using the polymerase chain reaction with degenerate DNA oligomers directed to the conserved tyrosine phosphatase domain, we identified 6 novel tyrosine phosphatases. One of these, PTP NE-3, is a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 74 publications
(47 reference statements)
4
45
0
Order By: Relevance
“…In particular, we have shown by chemical cross-linking that the ␣-latrotoxin/PTP complexes can form in brain membranes at a low physiologically relevant concentration of ␣-latrotoxin. Northern blotting data obtained by other groups indicate that the highest concentration of PTP is found in brain tissues (24,25,44), which is also compatible with its proposed role as a functional ␣-latrotoxin receptor.…”
Section: Figsupporting
confidence: 66%
See 1 more Smart Citation
“…In particular, we have shown by chemical cross-linking that the ␣-latrotoxin/PTP complexes can form in brain membranes at a low physiologically relevant concentration of ␣-latrotoxin. Northern blotting data obtained by other groups indicate that the highest concentration of PTP is found in brain tissues (24,25,44), which is also compatible with its proposed role as a functional ␣-latrotoxin receptor.…”
Section: Figsupporting
confidence: 66%
“…This membrane phosphatase was discovered independently in several laboratories and is known as PTP (24), PTP NE-3 (25), PTP-P1 (26), and LAR-PTP2 (27). Genetic studies in mouse and Drosophila identified PTP as a protein essential for neuronal development and axonal pathfinding (28 -30).…”
mentioning
confidence: 99%
“…whole-mouse embryo RNA and has an 80% sequence identity to human LAR (Strueli et al, 1988) in the intracellular domain. During the course of our work, the rat homolog of PTP NU-3 was reported by several laboratories, including LAR-PTP2 , PTP NE-3 (Walton et al, 1993), CPTP-1/3 (Sahin and Hockfield, 1993), PTP-PUPS (Pan et al, 1993) and HPTP-a (Yan et al, 1993). A series of NU-3 cDNAs were cloned by screening an 18.5-day p.c.…”
Section: Gac M T Gac Ggt Ttc Atc Gtg Gtc Tac Ctg Cct Gat Ggc Cag Act mentioning
confidence: 99%
“…This manuscript reports the molecular cloning and the identification of a unique splice form of NU-3, the murine homolog of the rat CAM tyrosine phosphatase known as LAR-PTP2 , PTP NE-3, (Walton et al, 1993), CPTP-1/3 (Sahin and Hockfield, 1993), PTP-Pl/PS (Pan et al, 1993) and RPTP-a (Yan et al, 1993).…”
mentioning
confidence: 99%
“…Among them, type II RPTPs are characterized by the presence of varying numbers of immunoglobulin (Ig)-like and fibronectin type III repeat (FN-III)-like domains in the extracellular regions and include LAR [9,10], PTP6 [11,12], PTPx [13], PTP/t [14], PTPa (NE-3) [15,16] and Drosophila DPTP [10]. Since these structural motifs are also utilized by cell adhesion molecules such as the neural cell adhesion molecule (N-CAM), it has been postulated that type II RPTPs might be involved in cell adhesion.…”
Section: Introductionmentioning
confidence: 99%